2018
DOI: 10.1177/0963689718787501
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy of Pulmonary Fibrosis

Abstract: Although the clinical application of new drugs has been shown to be effective in slowing disease progression and improving the quality of life in patients with pulmonary fibrosis, the damaged lung tissue does not recover with these drugs. Thus, there is an urgent need to establish regenerative therapy, such as stem cell therapy or tissue engineering. Moreover, the clinical application of mesenchymal stem cell (MSC) therapy has been shown to be safe in humans with idiopathic pulmonary fibrosis (IPF). It seems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 64 publications
0
36
0
1
Order By: Relevance
“…Interestingly, ASCs/MSCs have been reported as cellular therapy option for pulmonary fibrosis and bronchopulmonary dysplasia by regulating immune cells inside the lung tissue, modulating trans-differentiation of different cell types including fibroblasts, and secreting various growth factors [96,97]. Furthermore, these cells could be used in infectious diseases because of their immunosuppressive or immune enhancement effects depending on their cytokine production and on the context of the immune response [98].…”
Section: Ascs Mscs Obesity and Covid-19mentioning
confidence: 99%
“…Interestingly, ASCs/MSCs have been reported as cellular therapy option for pulmonary fibrosis and bronchopulmonary dysplasia by regulating immune cells inside the lung tissue, modulating trans-differentiation of different cell types including fibroblasts, and secreting various growth factors [96,97]. Furthermore, these cells could be used in infectious diseases because of their immunosuppressive or immune enhancement effects depending on their cytokine production and on the context of the immune response [98].…”
Section: Ascs Mscs Obesity and Covid-19mentioning
confidence: 99%
“…9 MSCs are considered to suppress the over-activated inflammatory response, promote recovery of lung function, and potentially influence the progress of pulmonary fibrosis. 10 Thus, the use of MSCs to improve the clinical outcome of the patients with severe cases of COVID-19 disease requires evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and animal studies suggest it is as effective as pharmaceutical therapies in treating PF. 129 Although they have uncertain mechanisms of action, MSCs have been proven to exert a modulating effect in lung inflammation and fibrosis. 130 Experimental models on human tissue and animal studies have also reported that MSCs achieve excellent outcomes in ALI/ARDS by attenuating the severity of lung injury and by reducing mortality.…”
Section: Discussionmentioning
confidence: 99%